THE EFFECTIVE OF SIMULATION STRATEGY ON SPEAKING COMPETENCE OF THE STUDENTS AT THE BUSINESS ADMINISTRATION DEPARTMENT OF SRIWIJAYA STATE POLYTECHNIC - Darmaliana; Nian Masna Evawati (Politeknik Negeri Sriwijaya, 2013)
The objective of this study was to find out whether or not there is`any significant effect in speaking competence of the students who are taught by using simulation strategy. This research conducted by using using quasi-experimental design. The population consisted of 188 students of the second semester students of Business Administration at State Polytechnic of Sriwijaya in academic year 2011/2012. Fourty of them were selected by using purposive random sampling based on some criteria. To collect data were used pre-test and post-test. The findings show that the students’ speaking competence increased significantly by 9.765. In other words, simulation strategy was effective to improve students’ speaking competence.